Infertile men's needs and assessment of fertility care. (1st October 2016) - Sylvest, Randi; Fürbringer, Jeanette Krogh; Schmidt, Lone; Pinborg, Anja
Abstract: Introduction: Male infertility is potentially a severe, low-control stressor. There is limited knowledge of the expectations, needs, and assessment of fertility care among men with severe infertility. The aim of this study was to explore experience, expectations, needs, and assessment of fertility care among Danish men having severe male-factor infertility. Methods: Semi-structured qualitative interview study with 10 men with very low sperm quality initiating intracytoplasmic sperm injection (ICSI) treatment at the Fertility Clinic, Copenhagen University Hospital, Hvidovre, Denmark. Five of the men participated in a follow-up interview after their first ICSI treatment. The data collection took place during November 2014 to May 2015. Data were analysed using qualitative content analysis. Results: Two themes were found: 'The maze' and 'Desire for care'. It felt like an eternity for the men from the referral until treatment started. The men did not understand the process, and it was like being in a maze. The men saw fatherhood as something to strive for. They felt that they could not do what a man is supposed to do, and they felt pushed aside and that treatment focused on the women. The men appreciated the staff's kindness and professionalism but desired the staff to address emotional subjects too. Conclusion: The process from referral to treatment felt like a maze for these men. They needed the staff to give them the opportunity to speak of the psychosocial consequences of severe male-factor infertility.